ANALISIS EKONOMI FUNGSI BIAYA PRODUKSI, PENETAPAN TARIF DAN ALOKASI AIR MINUM YANG EFISIEN: STUDI KASUS DI PDAM TIRTA DAROY KOTA BANDA ACEH - Yushar Yushar; Sofyan Syahnur (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2017)
The aim of this research is to explain the factors that affect the cost of clean water production, the level of efficiency of production costs, and calculate the cost of goods sold in PDAM Tirta Daroy. Estimation methods Ordinary Least Square (OLS) is used to estimate the parameters of the water production cost is the amount of water production and the rate of leakage. The analysis shows the number of water production affect positively and significantly to the cost of water production. In the regression analysis results obtained 1 +